The British at the gates the New Orleans campaign in the War of 1812 - Reilly, Robin (New York, Putnam, 1974)
In 1814, the final year of the War of 1812, Britain mounted a massive seaborne assault against the United States. The British burned Washington, forcing President Madison and his cabinet to flee, but the Americans succeeded in fending off an assault on Baltimore (commemorated in the words of the American National Anthem). By the end of 1812 the British had sailed southward to launch a bold attack on New Orleans, which was defeated by the Americans under the inspired leadership of Andrew Jackson.Reilly's account of the Battle of New Orleans and the events that led up to it was first published to great acclaim in 1974. It is still regarded by many experts as unsurpassed. This is the first paperback edition. The text has been reset and the maps redrawn, and there are more pictures.
Bibliography: p. 360-366.
74059
Keywords: United States -- History -- War of 1812; Louisiana New Orleans